The Influence of the Cost of Debt on Tax Avoidance with Managerial Opportunism and Company Size as Moderation Variables - Zafira, Aida; Taqi, Muhamad (SMART Insight, 2024)
Using managerial opportunism and firm size as moderators, this study will look at manufacturing businesses listed on the BEI from 2018 to 2022 and see how debt costs affect tax avoidance. This study used multiple linear regression analysis to draw conclusions from data collected from yearly financial reports posted on the BEI, which were selected using a purposive selection approach. Using SPSS software for data analysis, this research surveyed 54 manufacturing businesses that were listed on the Indonesia Stock Exchange between 2018 and 2022. Managerial opportunism and firm size both have the potential to amplify the favorable impact of debt costs on tax avoidance, according to this study's findings.